Prognostic significance of six autoantibodies in esophageal squamous cell carcinoma: A prospective multi‐institutional study - Fumiaki Shiratori; Naoto Fujiwara; Yasuaki Nakajima; Koji Otsuka; Masahiko Murakami; Satoru Matsuda; Hirofumi Kawakubo; Keita Takahashi; Yuichiro Tanishima; Daiji Oka; Shunichi Ito; Kosuke Narumiya; et al. (Annals of Gastroenterological Surgery)
Abstract Aim Serum autoantibodies have been reported to react with tumor‐associated antigens in various cancers. This study evaluated the diagnostic and prognostic significance of six autoantibody panels in esophageal squamous cell carcinoma. Methods In this study, 193 patients with esophageal squamous cell carcinoma and 78 healthy controls were enrolled. Serum antibodies were detected using originally developed enzyme‐linked immunosorbent assays to detect autoantibodies against the following tumor antigens: c‐myc, p62, RalA, p53, Sui1, and NY‐ESO‐1. The positive rates of the six‐autoantibody panel were compared with those of SCC antigen (SCC‐Ag). The prognostic significance of these autoantibodies was also evaluated. Results The overall positive rate was significantly higher in the six‐autoantibody panel than in SCC‐Ag (72% vs. 28%; p < 0.01). The positive rates of the six‐autoantibody panel were 71% in stage 0/I, 73% in stage II, and 71% in stage III. No clinicopathological factors were associated with autoantibodies. Although the difference was not significant, the overall survival of the autoantibody‐positive group was worse than that of the autoantibody‐negative group (p = 0.14). Conclusion The six‐autoantibody panel was useful for detecting esophageal squamous cell carcinoma, particularly in stage 0/I; however, it showed limited prognostic significance.